Modern Interpretation of Early Diagnosis of Prostate Cancer - Abdukadirovich, Rakmanov Xamza (Journal of Science in Medicine and Life, 2024)
On average, 70% of the normal prostate is composed of glandular elements and the remaining 30% is fibromuscular stroma. The glandular tissue of the prostate is usually composed of internal glands, which include the transition zone and periureteral glandular tissue, and external glands, which occupy the peripheral and central zones. TRUS can distinguish the transition zone, which is usually located anteriorly as a hypoechoic area, from the peripheral zone, which is echogenic and has a uniform echotexture compared to the rest of the gland. On the other hand, in healthy adult men, the central zone differs little from the peripheral zone. The transition zone is the main site of hyperplastic changes and makes up the majority of the prostate tissue in older men. It may be the site of development of about 20% of all prostate cancers. It should be noted that 1 to 5% of prostate cancers are located in the central zone. The peripheral zone, the main site of development of chronic prostatitis, causes about 70% of prostate cancer. On the other hand, cancer lesions in the transition zone are unlikely to be distinguished from BPH nodules by TRUS.